2014
DOI: 10.1248/bpb.b14-00037
|View full text |Cite
|
Sign up to set email alerts
|

Search for New Type of PPARγ Agonist-Like Anti-diabetic Compounds from Medicinal Plants

Abstract: Potent ligands of peroxisome proliferator-activated receptor γ (PPARγ) such as thiazolidinediones (pioglitazone, troglitazone, etc.) improve insulin sensitivity by increasing the levels of adiponectin, an important adipocytokine associated with insulin sensitivity in adipose tissue. Several constituents from medicinal plants were recently reported to show PPARγ agonist-like activity in 3T3-L1 cells, but did not show agonistic activity at the receptor site different from thiazolidinediones. Our recent studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
3
18
0
Order By: Relevance
“…Hydrangeic acid from the processed leaves of Hydrangea macrophylla var. thunbergii has been reported to have PPARγ agonistic activity . We further showed that SaR, ZR, EH and ScR were strongly bound to the PPARγ expressed in VAT of 20 week‐old male mice (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Hydrangeic acid from the processed leaves of Hydrangea macrophylla var. thunbergii has been reported to have PPARγ agonistic activity . We further showed that SaR, ZR, EH and ScR were strongly bound to the PPARγ expressed in VAT of 20 week‐old male mice (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Thus, searching for drugs with a similar clinical function, but fewer side effects has become a new direction of effort. Natural products are rich sources of drug discovery; thus, natural products are a focus of research …”
Section: Pparγ Agonists From Natural Productsmentioning
confidence: 99%
“…While there is no shortage of reviews on PPAR γ modulators12, 13, 14, including natural products, to the best of our knowledge, general reviews on natural PPAR α modulators are still lacking, although some papers have reported on the activity of certain classes of natural products 15 .…”
Section: Natural Products Modulating Pparαmentioning
confidence: 99%